2023
DOI: 10.1021/acsnano.3c07517
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Nanozymes Counteract Photoreceptor Degeneration and Retina Inflammation in a Light-Damage Model of Age-Related Macular Degeneration

Sara Cupini,
Stefano Di Marco,
Luca Boselli
et al.

Abstract: Degeneration of photoreceptors in age-related macular degeneration (AMD) is associated with oxidative stress due to the intense aerobic metabolism of rods and cones that if not properly counterbalanced by endogenous antioxidant mechanisms can precipitate photoreceptor degeneration. In spite of being a priority eye disease for its high incidence in the elderly, no effective treatments for AMD exist. While systemic administration of antioxidants has been unsuccessful in slowing down degeneration, locally adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…All of the nanozymes can oxidize TMB to show a blue color in a few minutes (Figure S4, Supporting Information), confirming that these NPs were peroxidase-mimicking nanozymes. The result further reported that the 5 nm PtNPs show much higher catalytic activity than CeNPs and AuNPs at the same concentration (1 nM) …”
Section: Resultsmentioning
confidence: 75%
“…All of the nanozymes can oxidize TMB to show a blue color in a few minutes (Figure S4, Supporting Information), confirming that these NPs were peroxidase-mimicking nanozymes. The result further reported that the 5 nm PtNPs show much higher catalytic activity than CeNPs and AuNPs at the same concentration (1 nM) …”
Section: Resultsmentioning
confidence: 75%
“…assessed the effectiveness of intravitreally injected Pt NPs in either preventing or alleviating light‐induced damage in dark‐reared rats and found that both preventive and post‐lesional IVT of Pt NPs led to increased photoreceptors after light damage, further indicating that Pt NPs can effectively disrupt the detrimental cycle that connects oxidative stress, degeneration, and inflammation by acting as both antioxidants and anti‐inflammatory agents. [ 176 ] Intriguingly, for RNV therapies, Xue et al. devised a Pt‐based nanozyme functioned with mitochondria‐targeted ability that can eliminate oxidative damage in RNV (Pt@MitoLipo) (Figure 8b).…”
Section: Nanocarriers For Ocular Posterior Drug Deliverymentioning
confidence: 99%